Three new species of the genus Xiphidiopsis Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Meconematinae) in China - Han, Li; Di, Juan-Xia; Chang, Yan-Lin; Shi, Fu-Ming (Zootaxa, 2015)
The article reported three new species of the genus Xiphidiopsis Redtenbacher, 1891 in China: Xiphidiopsis (Xiphidiopsis) minorincisus Han, Chang & Shi sp. nov., Xiphidiopsis (Xiphidiopsis) protensus Han, Chang & Shi sp. nov. and Xiphidiopsis (Xiphidiopsis) anisolobulus Han, Di & Shi sp. nov. The type material is deposited in the Museum of Hebei University, Baoding, P. R. China.